Oral mucosal lesions in skin diseased patients attending a dermatologic clinic: a cross-sectional study in Sudan - Salman Hussein; Ali Raouf W; Åstrøm Anne N; Suliman Nada M; Johannessen Anne C (BMC, 2011)
Abstract Background So far there have been no studies focusing on the prevalence of a wide spectrum of oral mucosal lesions (OML) in patients with dermatologic diseases. This is noteworthy as skin lesions are strongly associated with oral lesions and could easily be neglected by dentists. This study aimed to estimate the frequency and socio-behavioural correlates of OML in skin diseased patients attending outpatient's facility of Khartoum Teaching Hospital - Dermatology Clinic, Sudan. Methods A cross-sectional hospital-based study was conducted in Khartoum from October 2008 to January 2009. A total of 588 patients (mean age 37.2 ± 16 years, 50.3% females) completed an oral examination and a personal interview of which 544 patients (mean age 37.1 ± 15.9 years, 50% females) with confirmed skin disease diagnosis were included for further analyses. OML were recorded using the World Health Organization criteria (WHO). Biopsy and smear were used as adjuvant techniques for confirmation. Data were analysed using the Statistical Package for Social Science (Version 15.0.1). Cross tabulation and Chi-square with Fisher's exact test were used. Results A total of 438 OML were registered in 315 (57.9%, males: 54.6% versus females: 45.6%, p < 0.05) skin diseased patients. Thus, a certain number of patients had more than one type of OML. Tongue lesions were the most frequently diagnosed OML (23.3%), followed in descending order by white lesions (19.1%), red and blue lesions (11%) and vesiculobullous diseases (6%). OML in various skin diseases were; vesiculobullous reaction pattern (72.2%), lichenoid reaction pattern (60.5%), infectious lesions (56.5%), psoriasiform reaction pattern (56.7%), and spongiotic reaction pattern (46.8%). Presence of OML in skin diseased patients was most frequent in older age groups (62.4% older versus 52.7% younger, p < 0.05), in males (63.2% males versus 52.6% females, p < 0.05), patients with a systemic disease (65.2% with systemic versus 51.9% without systemic disease, p < 0.05) and among current users of smokeless tobacco (toombak) (77% current use versus 54.8% no use, p < 0.00). Conclusions OML were frequently diagnosed in skin diseased patients and varied systematically with age, gender, systemic condition and use of toombak. The high prevalence of OML emphasizes the importance of routine examination of oral mucosa in a dermatology clinic.